Migrating Thermal Tides in the Martian Atmosphere During Aphelion Season Observed by EMM/EMIRS. Issue 18 (16th September 2022) - Fan, Siteng; Forget, François; Smith, Michael D.; Guerlet, Sandrine; Badri, Khalid M.; Atwood, Samuel A.; Young, Roland M. B.; Edwards, Christopher S.; Christensen, Philip R.; Deighan, Justin; Al Matroushi, Hessa R.; Bierjon, Antoine; et al.
Abstract: Temperature profiles retrieved using the first set of data of the Emirates Mars InfraRed Spectrometer obtained during the science phase of the Emirates Mars Mission are used for the analysis of migrating thermal tides in the Martian atmosphere. The selected data cover a solar longitude ( L S ) range of 60°–90° of Martian Year 36. The novel orbit design of the Hope Probe leads to a good geographic and local time coverage that significantly improves the analysis. Wave mode decomposition suggests dominant diurnal tide and important semi‐diurnal tide with maximal amplitudes of 6 and 2 K, respectively, as well as the existence of ∼0.5 K ter‐diurnal tide. The results agree well with predictions by the Mars Planetary Climate Model, but the observed diurnal tide has an earlier phase (3 hr), and the semi‐diurnal tide has an unexpectedly large wavelength (∼200 km). Plain Language Summary: As a result of its small thickness, the Martian atmosphere experiences large temperature variations within each Martian day due to the incoming sunlight. Such rapid and large temperature variations excite waves propagating in the Martian atmosphere that highly influence winds, cloud formation, and dust transport. In this work, we use the atmospheric temperature measurements derived using observations obtained by an infrared spectrometer onboard the Hope Probe to analyze the diurnal temperature variations and the excited waves. The novel design of the spacecraft's orbit provides good data coverage in location and time, leading to the success of detailed analyses of the waves that propagate in the Martian atmosphere synchronously with the movement of the Sun, among which a new wave mode with a period of one third of a Martian day is detected. We compare the results with predictions provided by numerical simulations, and they show good agreements in the wave strengths, but the observed waves have different wavelengths and phases. Key Points: Migrating thermal tides in the Martian atmosphere are analyzed using the first set of Emirates Mars Mission/Emirates Mars InfraRed Spectrometer observations The observed amplitudes of diurnal and semi‐diurnal tides agree well with model predictions, but with different phases and wavelengths Ter‐diurnal tide is detected with an amplitude of ∼0.5 K, due to the observations covering the full range of local times